Expression of recombinant G-CSF receptor domains and their inhibitory role on G-CSF function - Hamid Bakherad; Neda Setayesh; Seyed Latif Mousavi Gargari; Walead Ebrahimizadeh; Faranak Mavandadnejad; Elnaz Faghfuri; Soheila Ebrahimi; Mohammad Heiat; Mona Shahpari; Zargham Sepehrizadeh (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Granulocyte colony-stimulating factor (G-CSF) is routinely used in combination with chemotherapy to battle neutropenia. However, studies suggest that this chemokine may increase the risk of metastasis and malignancy in many cancers. To counteract the adverse effects of G-CSF in cancer, antibodies have been used to block its action. However, antibodies are large and complex molecules which makes their production expensive. Thus in this study, we aim to construct different structure variants of the G-CSF receptor containing different domains and select the best variant that prevents the adverse actions of this chemokine. These novel structures are smaller than antibodies and easier to produce. Experimental approach: Different domains of the G-CSF receptor were designed and cloned into the pET28a expression vector. These recombinant receptor subunits were then expressed in Escherichia coli and purified using standard affinity chromatography techniques. Interaction of recombinant receptor subunits with G-CSF was assessed using enzyme-linked immunosorbent assay and NFS60 cells. Findings / Results: Two recombinant receptor subunits containing D1 + D2 + D3 domains and D2 domain showed the strongest inhibitory activity to G-CSF. Conclusion and implications: These novel recombinant receptor variants could be candidates for further studies in the development of novel therapeutics.